2022
DOI: 10.3390/joitmc8030123
|View full text |Cite
|
Sign up to set email alerts
|

Lean and Green Product Development in SMEs: A Comparative Study between Small- and Medium-Sized Brazilian and Japanese Enterprises

Abstract: Facing the new challenges in production processes, companies should adopt lean and green practices in product development. In SMEs, the application of these practices is more complex. This work explores the maturity of lean–green methodologies in the product development process in Brazilian and Japanese SMEs. The methodology used is multicriteria, combining the analytic hierarchy process (AHP) and TOPSIS 2-tuple method, applied to four Japanese SMEs and four Brazilian SMEs in the metalworking sector. The crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 98 publications
(127 reference statements)
0
12
0
Order By: Relevance
“…Meanwhile, Nor-Aishah et al (2020) and Hanaysha et al (2022) measured the sustainable performance of SMEs in a holistic manner, which consisted of three aspects known as economic, environmental and social sustainability. In some other previous studies, researchers focused on the adoption of "lean and green thinking" in achieving efficiency in production and reducing waste (Caldera et al, 2019), implementation of "lean thinking" in directing business firms towards sustainability practices (Franco & Rodrigues, 2021), application of "lean-green operations" in new product development for efficiency (Oliveira et al, 2022), green manufacturing practices and green innovation for corporate sustainable performance (Al-Hakimi et al, 2022), sustainable product and process design, sustainable waste disposal management, sustainable human resource management and local community development (Mitra, 2023) and, performing sustainable manufacturing practices which focused on using economically-sound processes to reduce negative environmental impacts in products production (Ali & Johl, 2023). It could be said that although many organizations have adopted sustainable practices, there remains no uniformed reporting standard and measurement of sustainable performance in which firms measure different things and report in different ways (Byrne, 2023;Ribeiro, 2023).…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…Meanwhile, Nor-Aishah et al (2020) and Hanaysha et al (2022) measured the sustainable performance of SMEs in a holistic manner, which consisted of three aspects known as economic, environmental and social sustainability. In some other previous studies, researchers focused on the adoption of "lean and green thinking" in achieving efficiency in production and reducing waste (Caldera et al, 2019), implementation of "lean thinking" in directing business firms towards sustainability practices (Franco & Rodrigues, 2021), application of "lean-green operations" in new product development for efficiency (Oliveira et al, 2022), green manufacturing practices and green innovation for corporate sustainable performance (Al-Hakimi et al, 2022), sustainable product and process design, sustainable waste disposal management, sustainable human resource management and local community development (Mitra, 2023) and, performing sustainable manufacturing practices which focused on using economically-sound processes to reduce negative environmental impacts in products production (Ali & Johl, 2023). It could be said that although many organizations have adopted sustainable practices, there remains no uniformed reporting standard and measurement of sustainable performance in which firms measure different things and report in different ways (Byrne, 2023;Ribeiro, 2023).…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…The studies linking LM to the PDP encompass performance evaluations (de Toledo et al. , 2023), maturity assessments (Oliveira et al. , 2022; Sassanelli et al.…”
Section: Current Literature On Industry 40 and Lean Manufacturing In ...mentioning
confidence: 99%
“…Throughout the phases of the PDP, integrating external knowledge with internal knowledge plays a crucial role in enhancing design quality and MP for new products, fostering synergy within the organisation (Benitez et al, 2022). Notably, several authors have suggested that LM principles can serve as catalysts for achieving superior market performance in the PDP (de Toledo et al, 2023;Dahmani et al, 2022;Francisco et al, 2022;Oliveira et al, 2022;Reis et al, 2021;Varl et al, 2020;Marodin et al, 2018). Therefore, the objective of our study is to investigate the potential positive association between LM and the various phases of the PDP, focussing on improving efficiency in terms of MP.…”
Section: Lean Manufacturing and Pdp Association With Market Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Lean is considered to be a management practice that improves organizational performance, ultimately leading to sustainability; hence SMEs adopt lean principles in their operations [16]. Furthermore, while facing new challenges in production processes, companies should adopt lean and green practices in product development [19].…”
Section: Literature Reviewmentioning
confidence: 99%